Professional integrity in higher education: Behind the green curtain in the land of Oz - Crews, Gordon A. (American journal of criminal justice, 2006)
This article discusses concerns related to professional integrity in academics and to the use of collegiality as an informal criterion for employment and evaluation decisions. We question the nature of the educational enterprise and the academic environment within which both students and faculty operate. We use the AAUP Statement on Professional Ethics to guide our examination of collegiality, and the three traditional areas of faculty evaluation (teaching, scholarship, and service), as they relate to professional integrity. We discuss potential pitfalls in situations involving integrity concerns, and suggest that the use of collegiality in professional decisions is more prevalent and potentially harmful than many realize.